index 1be499b..61d2964 100644 (file)
@@ -1,10 +1,9 @@
[[!toc]]

-
------------------------------

-This thread develops an idea based on a detailed suggestion of Ken
+This topic develops an idea based on a detailed suggestion of Ken
Shan's.  We'll build a series of functions that operate on trees,
doing various things, including replacing leaves, counting nodes, and
converting a tree to a list of leaves.  The end result will be an
@@ -12,295 +11,301 @@ application for continuations.

From an engineering standpoint, we'll build a tree transformer that
deals in monads.  We can modify the behavior of the system by swapping
a layer of funtionality without disturbing the underlying system, for
of intensionality to an extensional grammar, but we have not yet seen
-the utility of replacing one monad with other.)
+the utility of replacing one monad with other.

-First, we'll be needing a lot of trees during the remainder of the
-course.  Here's a type constructor for binary trees:
+First, we'll be needing a lot of trees for the remainder of the
+course.  Here again is a type constructor for leaf-labeled, binary trees:

type 'a tree = Leaf of 'a | Node of ('a tree * 'a tree)

-These are trees in which the internal nodes do not have labels.  [How
-would you adjust the type constructor to allow for labels on the
+[How would you adjust the type constructor to allow for labels on the
internal nodes?]

We'll be using trees where the nodes are integers, e.g.,

-<pre>
-let t1 = Node ((Node ((Leaf 2), (Leaf 3))),
-               (Node ((Leaf 5),(Node ((Leaf 7),
-                                      (Leaf 11))))))
-
-    .
- ___|___
- |     |
- .     .
-_|__  _|__
-|  |  |  |
-2  3  5  .
-        _|__
-        |  |
-        7  11
-</pre>
+       let t1 = Node (Node (Leaf 2, Leaf 3),
+                      Node (Leaf 5, Node (Leaf 7,
+                                             Leaf 11)))
+           .
+        ___|___
+        |     |
+        .     .
+       _|_   _|__
+       |  |  |  |
+       2  3  5  .
+               _|__
+               |  |
+               7  11

Our first task will be to replace each leaf with its double:

-<pre>
-let rec treemap (newleaf:'a -> 'b) (t:'a tree):('b tree) =
-  match t with Leaf x -> Leaf (newleaf x)
-             | Node (l, r) -> Node ((treemap newleaf l),
-                                    (treemap newleaf r));;
-</pre>
-`treemap` takes a function that transforms old leaves into new leaves,
+       let rec tree_map (leaf_modifier : 'a -> 'b) (t : 'a tree) : 'b tree =
+         match t with
+           | Leaf i -> Leaf (leaf_modifier i)
+           | Node (l, r) -> Node (tree_map leaf_modifier l,
+                                  tree_map leaf_modifier r);;
+
+`tree_map` takes a function that transforms old leaves into new leaves,
and maps that function over all the leaves in the tree, leaving the
structure of the tree unchanged.  For instance:

-<pre>
-let double i = i + i;;
-treemap double t1;;
-- : int tree =
-Node (Node (Leaf 4, Leaf 6), Node (Leaf 10, Node (Leaf 14, Leaf 22)))
-
-    .
- ___|____
- |      |
- .      .
-_|__  __|__
-|  |  |   |
-4  6  10  .
-        __|___
-        |    |
-        14   22
-</pre>
-
-We could have built the doubling operation right into the `treemap`
-code.  However, because what to do to each leaf is a parameter, we can
+       let double i = i + i;;
+       tree_map double t1;;
+       - : int tree =
+       Node (Node (Leaf 4, Leaf 6), Node (Leaf 10, Node (Leaf 14, Leaf 22)))
+
+           .
+        ___|____
+        |      |
+        .      .
+       _|__  __|__
+       |  |  |   |
+       4  6  10  .
+               __|___
+               |    |
+               14   22
+
+We could have built the doubling operation right into the `tree_map`
+code.  However, because we've left what to do to each leaf as a parameter, we can
decide to do something else to the leaves without needing to rewrite
-`treemap`.  For instance, we can easily square each leaf instead by
+`tree_map`.  For instance, we can easily square each leaf instead by
supplying the appropriate `int -> int` operation in place of `double`:

-<pre>
-let square x = x * x;;
-treemap square t1;;
-- : int tree =ppp
-Node (Node (Leaf 4, Leaf 9), Node (Leaf 25, Node (Leaf 49, Leaf 121)))
-</pre>
+       let square i = i * i;;
+       tree_map square t1;;
+       - : int tree =ppp
+       Node (Node (Leaf 4, Leaf 9), Node (Leaf 25, Node (Leaf 49, Leaf 121)))

-Note that what `treemap` does is take some global, contextual
+Note that what `tree_map` does is take some unchanging contextual
information---what to do to each leaf---and supplies that information
-to each subpart of the computation.  In other words, `treemap` has the
+to each subpart of the computation.  In other words, `tree_map` has the

-In general, we're on a journey of making our treemap function more and
-more flexible.  So the next step---combining the tree transducer with
-tree that is ready to accept any `int->int` function and produce the
+In general, we're on a journey of making our `tree_map` function more and
+more flexible.  So the next step---combining the tree transformer with
+tree that is ready to accept any `int -> int` function and produce the
updated tree.

-\tree (. (. (f2) (f3))(. (f5) (.(f7)(f11))))
-<pre>
-\f    .
-  ____|____
-  |       |
-  .       .
-__|__   __|__
-|   |   |   |
-f2  f3  f5  .
-          __|___
-          |    |
-          f7  f11
-</pre>
+\tree (. (. (f 2) (f 3)) (. (f 5) (. (f 7) (f 11))))
+
+       \f      .
+          _____|____
+          |        |
+          .        .
+        __|___   __|___
+        |    |   |    |
+       f 2  f 3  f 5  .
+                    __|___
+                    |    |
+                   f 7  f 11

That is, we want to transform the ordinary tree `t1` (of type `int
-tree`) into a reader object of type `(int->int)-> int tree`: something
-that, when you apply it to an `int->int` function returns an `int
-tree` in which each leaf `x` has been replaced with `(f x)`.
+tree`) into a reader object of type `(int -> int) -> int tree`: something
+that, when you apply it to an `int -> int` function `f` returns an `int
+tree` in which each leaf `i` has been replaced with `f i`.

With previous readers, we always knew which kind of environment to
expect: either an assignment function (the original calculator
simulation), a world (the intensionality monad), an integer (the
-enough for now to expect that our reader will expect a function of
-type `int->int`.
-
-<pre>
-type 'a reader = (int->int) -> 'a;;  (* mnemonic: e for environment *)
-</pre>
-
-It's easy to figure out how to turn an `int` into an `int reader`:
-
-<pre>
-let int2int_reader (x:'a): 'b reader = fun (op:'a -> 'b) -> op x;;
-int2int_reader 2 (fun i -> i + i);;
-- : int = 4
-</pre>
-
-But what do we do when the integers are scattered over the leaves of a
-tree?  A binary tree is not the kind of thing that we can apply a
-function of type `int->int` to.
-
-<pre>
-  match t with Leaf x -> reader_bind (f x) (fun x' -> reader_unit (Leaf x'))
-             | Node (l, r) -> reader_bind (treemonadizer f l) (fun x ->
-</pre>
+Jacobson-inspired link monad), etc.  In the present case, we expect that our "environment" will be some function of type `int -> int`. "Looking up" some `int` in the environment will return us the `int` that comes out the other side of that function.
+
+       type 'a reader = (int -> int) -> 'a;;  (* mnemonic: e for environment *)
+       let reader_unit (a : 'a) : 'a reader = fun _ -> a;;
+       let reader_bind (u: 'a reader) (f : 'a -> 'b reader) : 'b reader = fun e -> f (u e) e;;
+
+It would be a simple matter to turn an *integer* into an `int reader`:
+
+       let int_readerize : int -> int reader = fun (a : int) -> fun (modifier : int -> int) -> modifier a;;
+       int_readerize 2 (fun i -> i + i);;
+       - : int = 4
+
+But how do we do the analagous transformation when our `int`s are scattered over the leaves of a tree? How do we turn an `int tree` into a reader?
+A tree is not the kind of thing that we can apply a
+function of type `int -> int` to.
+
+But we can do this:
+
+       let rec tree_monadize (f : 'a -> 'b reader) (t : 'a tree) : 'b tree reader =
+           match t with
+           | Leaf i -> reader_bind (f i) (fun i' -> reader_unit (Leaf i'))
+           | Node (l, r) -> reader_bind (tree_monadize f l) (fun x ->

This function says: give me a function `f` that knows how to turn
-something of type `'a` into an `'b reader`, and I'll show you how to
-turn an `'a tree` into an `'a tree reader`.  In more fanciful terms,
-the `treemonadizer` function builds plumbing that connects all of the
-leaves of a tree into one connected monadic network; it threads the
-
-<pre>
-- : int tree =
-Node (Node (Leaf 4, Leaf 6), Node (Leaf 10, Node (Leaf 14, Leaf 22)))
-</pre>
+something of type `'a` into an `'b reader`---this is a function of the same type that you could bind an `'a reader` to---and I'll show you how to
+turn an `'a tree` into an `'b tree reader`.  That is, if you show me how to do this:
+
+                     ------------
+         1     --->  |    1     |
+                     ------------
+
+then I'll give you back the ability to do this:
+
+                     ____________
+         .           |    .     |
+       __|___  --->  |  __|___  |
+       |    |        |  |    |  |
+       1    2        |  1    2  |
+                     ------------
+
+And how will that boxed tree behave? Whatever actions you perform on it will be transmitted down to corresponding operations on its leaves. For instance, our `int reader` expects an `int -> int` environment. If supplying environment `e` to our `int reader` doubles the contained `int`:
+
+                     ------------
+         1     --->  |    1     |  applied to e  ~~>  2
+                     ------------
+
+Then we can expect that supplying it to our `int tree reader` will double all the leaves:
+
+                     ____________
+         .           |    .     |                      .
+       __|___  --->  |  __|___  | applied to e  ~~>  __|___
+       |    |        |  |    |  |                    |    |
+       1    2        |  1    2  |                    2    4
+                     ------------
+
+In more fanciful terms, the `tree_monadize` function builds plumbing that connects all of the leaves of a tree into one connected monadic network; it threads the
+
+       - : int tree =
+       Node (Node (Leaf 4, Leaf 6), Node (Leaf 10, Node (Leaf 14, Leaf 22)))

Here, our environment is the doubling function (`fun i -> i + i`).  If
-int2int_reader t1`) to a different `int->int` function---say, the
+int_readerize t1`) to a different `int -> int` function---say, the
squaring function, `fun i -> i * i`---we get an entirely different
result:

-<pre>
-- : int tree =
-Node (Node (Leaf 4, Leaf 9), Node (Leaf 25, Node (Leaf 49, Leaf 121)))
-</pre>
+       - : int tree =
+       Node (Node (Leaf 4, Leaf 9), Node (Leaf 25, Node (Leaf 49, Leaf 121)))

-Now that we have a tree transducer that accepts a monad as a
+Now that we have a tree transformer that accepts a *reader* monad as a
parameter, we can see what it would take to swap in a different monad.
-For instance, we can use a state monad to count the number of nodes in
+
+For instance, we can use a state monad to count the number of leaves in
the tree.

-<pre>
-type 'a state = int -> 'a * int;;
-let state_unit x i = (x, i+.5);;
-let state_bind u f i = let (a, i') = u i in f a (i'+.5);;
-</pre>
+       type 'a state = int -> 'a * int;;
+       let state_unit a = fun s -> (a, s);;
+       let state_bind u f = fun s -> let (a, s') = u s in f a s';;

-Gratifyingly, we can use the `treemonadizer` function without any
+Gratifyingly, we can use the `tree_monadize` function without any
modification whatsoever, except for replacing the (parametric) type
-
-<pre>
-let rec treemonadizer (f:'a -> 'b state) (t:'a tree):('b tree) state =
-  match t with Leaf x -> state_bind (f x) (fun x' -> state_unit (Leaf x'))
-             | Node (l, r) -> state_bind (treemonadizer f l) (fun x ->
-                                state_bind (treemonadizer f r) (fun y ->
-                                  state_unit (Node (x, y))));;
-</pre>
-
-Then we can count the number of nodes in the tree:
-
-<pre>
-- : int tree * int =
-(Node (Node (Leaf 2, Leaf 3), Node (Leaf 5, Node (Leaf 7, Leaf 11))), 13)
-
-    .
- ___|___
- |     |
- .     .
-_|__  _|__
-|  |  |  |
-2  3  5  .
-        _|__
-        |  |
-        7  11
-</pre>
-
-Notice that we've counted each internal node twice---it's a good
-exercise to adjust the code to count each node once.
+`'b reader` with `'b state`, and substituting in the appropriate unit and bind:
+
+       let rec tree_monadize (f : 'a -> 'b state) (t : 'a tree) : 'b tree state =
+           match t with
+           | Leaf i -> state_bind (f i) (fun i' -> state_unit (Leaf i'))
+           | Node (l, r) -> state_bind (tree_monadize f l) (fun x ->
+                              state_bind (tree_monadize f r) (fun y ->
+                                state_unit (Node (x, y))));;
+
+Then we can count the number of leaves in the tree:
+
+       # tree_monadize (fun a -> fun s -> (a, s+1)) t1 0;;
+       - : int tree * int =
+       (Node (Node (Leaf 2, Leaf 3), Node (Leaf 5, Node (Leaf 7, Leaf 11))), 5)
+
+           .
+        ___|___
+        |     |
+        .     .
+       _|__  _|__
+       |  |  |  |
+       2  3  5  .
+               _|__
+               |  |
+               7  11
+
+Why does this work? Because the operation `fun a -> fun s -> (a, s+1)` takes an `int` and wraps it in an `int state` monadic box that increments the state. When we give that same operations to our `tree_monadize` function, it then wraps an `int tree` in a box, one that does the same state-incrementing for each of its leaves.

One more revealing example before getting down to business: replacing
-`state` everywhere in `treemonadizer` with `list` gives us
+`state` everywhere in `tree_monadize` with `list` gives us

-<pre>
-# treemonadizer (fun x -> [ [x; square x] ]) t1;;
-- : int list tree list =
-[Node
-  (Node (Leaf [2; 4], Leaf [3; 9]),
-   Node (Leaf [5; 25], Node (Leaf [7; 49], Leaf [11; 121])))]
-</pre>
+       # tree_monadize (fun i -> [ [i; square i] ]) t1;;
+       - : int list tree list =
+       [Node
+         (Node (Leaf [2; 4], Leaf [3; 9]),
+          Node (Leaf [5; 25], Node (Leaf [7; 49], Leaf [11; 121])))]

Unlike the previous cases, instead of turning a tree into a function
from some input to a result, this transformer replaces each `int` with
-a list of `int`'s.
+a list of `int`'s. We might also have done this with a Reader Monad, though then our environments would need to be of type `int -> int list`. Experiment with what happens if you supply the `tree_monadize` based on the List Monad an operation like `fun -> [ i; [2*i; 3*i] ]`. Use small trees for your experiment.

-Now for the main point.  What if we wanted to convert a tree to a list
-of leaves?

-<pre>
-type ('a, 'r) continuation = ('a -> 'r) -> 'r;;
-let continuation_unit x c = c x;;
-let continuation_bind u f c = u (fun a -> f a c);;
+<!--
+FIXME: We don't make it clear why the fun has to be int -> int list list, instead of int -> int list
+-->

-let rec treemonadizer (f:'a -> ('b, 'r) continuation) (t:'a tree):(('b tree), 'r) continuation =
-  match t with Leaf x -> continuation_bind (f x) (fun x' -> continuation_unit (Leaf x'))
-             | Node (l, r) -> continuation_bind (treemonadizer f l) (fun x ->
-                                continuation_bind (treemonadizer f r) (fun y ->
-                                  continuation_unit (Node (x, y))));;
-</pre>
+
+Now for the main point.  What if we wanted to convert a tree to a list
+of leaves?
+
+       type ('a, 'r) continuation = ('a -> 'r) -> 'r;;
+       let continuation_unit a = fun k -> k a;;
+       let continuation_bind u f = fun k -> u (fun a -> f a k);;
+
+       let rec tree_monadize (f : 'a -> ('b, 'r) continuation) (t : 'a tree) : ('b tree, 'r) continuation =
+           match t with
+           | Leaf i -> continuation_bind (f i) (fun i' -> continuation_unit (Leaf i'))
+           | Node (l, r) -> continuation_bind (tree_monadize f l) (fun x ->
+                              continuation_bind (tree_monadize f r) (fun y ->
+                                continuation_unit (Node (x, y))));;

We use the continuation monad described above, and insert the
-`continuation` type in the appropriate place in the `treemonadizer` code.
-We then compute:
+`continuation` type in the appropriate place in the `tree_monadize` code. Then if we give the `tree_monadize` function an operation that converts `int`s into continuations expecting `'b` arguments, it will give us back a way to turn `int tree`s into continuations that expect `'b tree` arguments. The effect of giving the continuation such an argument will be to distribute across the `'b tree`'s leaves effects that parallel the effects that the `'b`-expecting continuations would have on their `'b`s.

-<pre>
-# treemonadizer (fun a c -> a :: (c a)) t1 (fun t -> []);;
-- : int list = [2; 3; 5; 7; 11]
-</pre>
+So for example, we compute:

-We have found a way of collapsing a tree into a list of its leaves.
+       # tree_monadize (fun a -> fun k -> a :: (k a)) t1 (fun t -> []);;
+       - : int list = [2; 3; 5; 7; 11]
+
+We have found a way of collapsing a tree into a list of its leaves. Can you trace how this is working?

The continuation monad is amazingly flexible; we can use it to
simulate some of the computations performed above.  To see how, first
-note that an interestingly uninteresting thing happens if we use the
-continuation unit as our first argument to `treemonadizer`, and then
+note that an interestingly uninteresting thing happens if we use
+`continuation_unit` as our first argument to `tree_monadize`, and then
apply the result to the identity function:

-<pre>
-# treemonadizer continuation_unit t1 (fun x -> x);;
-- : int tree =
-Node (Node (Leaf 2, Leaf 3), Node (Leaf 5, Node (Leaf 7, Leaf 11)))
-</pre>
+       # tree_monadize continuation_unit t1 (fun i -> i);;
+       - : int tree =
+       Node (Node (Leaf 2, Leaf 3), Node (Leaf 5, Node (Leaf 7, Leaf 11)))

That is, nothing happens.  But we can begin to substitute more
-interesting functions for the first argument of `treemonadizer`:
-
-<pre>
-(* Simulating the tree reader: distributing a operation over the leaves *)
-# treemonadizer (fun a c -> c (square a)) t1 (fun x -> x);;
-- : int tree =
-Node (Node (Leaf 4, Leaf 9), Node (Leaf 25, Node (Leaf 49, Leaf 121)))
-
-(* Simulating the int list tree list *)
-# treemonadizer (fun a c -> c [a; square a]) t1 (fun x -> x);;
-- : int list tree =
-Node
- (Node (Leaf [2; 4], Leaf [3; 9]),
-  Node (Leaf [5; 25], Node (Leaf [7; 49], Leaf [11; 121])))
-
-(* Counting leaves *)
-# treemonadizer (fun a c -> 1 + c a) t1 (fun x -> 0);;
-- : int = 5
-</pre>
+interesting functions for the first argument of `tree_monadize`:
+
+       (* Simulating the tree reader: distributing a operation over the leaves *)
+       # tree_monadize (fun a -> fun k -> k (square a)) t1 (fun i -> i);;
+       - : int tree =
+       Node (Node (Leaf 4, Leaf 9), Node (Leaf 25, Node (Leaf 49, Leaf 121)))
+
+       (* Simulating the int list tree list *)
+       # tree_monadize (fun a -> fun k -> k [a; square a]) t1 (fun i -> i);;
+       - : int list tree =
+       Node
+        (Node (Leaf [2; 4], Leaf [3; 9]),
+         Node (Leaf [5; 25], Node (Leaf [7; 49], Leaf [11; 121])))
+
+       (* Counting leaves *)
+       # tree_monadize (fun a -> fun k -> 1 + k a) t1 (fun i -> 0);;
+       - : int = 5

We could simulate the tree state example too, but it would require
-generalizing the type of the continuation monad to
+generalizing the type of the continuation monad to
+
+       type ('a, 'b, 'c) continuation = ('a -> 'b) -> 'c;;
+
+If you want to see how to parameterize the definition of the `tree_monadize` function, so that you don't have to keep rewriting it for each new monad, see [this code](/code/tree_monadize.ml).

-    type ('a -> 'b -> 'c) continuation = ('a -> 'b) -> 'c;;

---------------------
@@ -308,79 +313,74 @@ The binary tree monad
Of course, by now you may have realized that we have discovered a new

-<pre>
-type 'a tree = Leaf of 'a | Node of ('a tree) * ('a tree);;
-let tree_unit (x:'a) = Leaf x;;
-let rec tree_bind (u:'a tree) (f:'a -> 'b tree):'b tree =
-  match u with Leaf x -> f x
-             | Node (l, r) -> Node ((tree_bind l f), (tree_bind r f));;
-</pre>
+       type 'a tree = Leaf of 'a | Node of ('a tree) * ('a tree);;
+       let tree_unit (a: 'a) = Leaf a;;
+       let rec tree_bind (u : 'a tree) (f : 'a -> 'b tree) : 'b tree =
+           match u with
+           | Leaf a -> f a
+           | Node (l, r) -> Node ((tree_bind l f), (tree_bind r f));;

For once, let's check the Monad laws.  The left identity law is easy:

-    Left identity: bind (unit a) f = bind (Leaf a) f = fa
+    Left identity: bind (unit a) f = bind (Leaf a) f = f a

To check the other two laws, we need to make the following
observation: it is easy to prove based on `tree_bind` by a simple
induction on the structure of the first argument that the tree
resulting from `bind u f` is a tree with the same strucure as `u`,
-except that each leaf `a` has been replaced with `fa`:
-
-\tree (. (fa1) (. (. (. (fa2)(fa3)) (fa4)) (fa5)))
-<pre>
-                .                         .
-              __|__                     __|__
-              |   |                     |   |
-              a1  .                    fa1  .
-                 _|__                     __|__
-                 |  |                     |   |
-                 .  a5                    .  fa5
-   bind         _|__       f   =        __|__
-                |  |                    |   |
-                .  a4                   .  fa4
-              __|__                   __|___
-              |   |                   |    |
-              a2  a3                 fa2  fa3
-</pre>
+except that each leaf `a` has been replaced with `f a`:
+
+\tree (. (f a1) (. (. (. (f a2) (f a3)) (f a4)) (f a5)))
+
+                       .                         .
+                     __|__                     __|__
+                     |   |                     |   |
+                     a1  .                   f a1  .
+                        _|__                     __|__
+                        |  |                     |   |
+                        .  a5                    .  f a5
+          bind         _|__       f   =        __|__
+                       |  |                    |   |
+                       .  a4                   .  f a4
+                     __|__                   __|___
+                     |   |                   |    |
+                     a2  a3                f a2  f a3

Given this equivalence, the right identity law

-    Right identity: bind u unit = u
+       Right identity: bind u unit = u

falls out once we realize that

-    bind (Leaf a) unit = unit a = Leaf a
+       bind (Leaf a) unit = unit a = Leaf a

As for the associative law,

-    Associativity: bind (bind u f) g = bind u (\a. bind (fa) g)
+       Associativity: bind (bind u f) g = bind u (\a. bind (f a) g)

we'll give an example that will show how an inductive proof would
proceed.  Let `f a = Node (Leaf a, Leaf a)`.  Then

-\tree (. (. (. (. (a1)(a2)))))
-\tree (. (. (. (. (a1) (a1)) (. (a1) (a1)))  ))
-<pre>
-                                           .
-                                       ____|____
-          .               .            |       |
-bind    __|__   f  =    __|_    =      .       .
-        |   |           |   |        __|__   __|__
-        a1  a2         fa1 fa2       |   |   |   |
-                                     a1  a1  a1  a1
-</pre>
+\tree (. (. (. (. (a1) (a2)))))
+\tree (. (. (. (. (a1) (a1)) (. (a1) (a1)))))
+
+                                                  .
+                                              ____|____
+                 .               .            |       |
+       bind    __|__   f  =    __|_    =      .       .
+               |   |           |   |        __|__   __|__
+               a1  a2        f a1 f a2      |   |   |   |
+                                            a1  a1  a1  a1

Now when we bind this tree to `g`, we get

-<pre>
-           .
-       ____|____
-       |       |
-       .       .
-     __|__   __|__
-     |   |   |   |
-    ga1 ga1 ga1 ga1
-</pre>
+                   .
+              _____|______
+              |          |
+              .          .
+            __|__      __|__
+            |   |      |   |
+          g a1 g a1  g a1 g a1

At this point, it should be easy to convince yourself that
using the recipe on the right hand side of the associative law will
@@ -391,6 +391,5 @@ So binary trees are a monad.